KUALITAS PELAYANAN RESTORAN BALKONDES DI SEKITAR KAWASAN CANDI BOROBUDUR - Ita Maemunah; Ratih Fitria; Dodi Affandi (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2019)
Research on the Service Quality of Balkondes Restaurants around the Borobudur Temple area was carried out to solve the problem of the level of business competition in the market space, as well as the low targets in achieving what Balkondes restaurants must achieve. This research was conducted to identify the wants and needs of restaurant-restaurant customers around Borobudur Temple, so that they can innovate the applied service strategies. This study uses a descriptive research method approach with data collection techniques through interviews; questionnaire; and literature study. The population in this study were balkondes in the Borobudur Temple area with a non-random sample technique, namely accidental sampling. Broadly speaking, the results of this study indicate that customers give good scores on the aspects of ease of location, comfort of the place, speed of presentation, explanation of waiters and attitude of response to customer complaints, while other aspects studied are only given sufficient scores.